Modelling of hull roughness. (15th February 2019) - Speranza, N.; Kidd, B.; Schultz, M.P.; Viola, I.M.
Abstract: In this paper we present a practical guideline on how to estimate the frictional resistance of ship hulls due to different fouling control coatings. Most of the current methods rely on empirical formulations based on an equivalent sand grain roughness height. These correlations are not universal and cannot be applied to every marine surface. Conversely, the shear stress of a specific coating can be measured in an experimental facility at the same Reynolds roughness number as at full scale. The results can be used to inform the boundary conditions of computational fluid dynamics, where the complex flow around the ship can be computed for any sailing condition. Hence, this methodology allows the estimation of the frictional resistance due to a specific surface in a specific sailing condition. Representative antifouling coating products by AkzoNobel, and wall functions for the open-source code OpenFOAM, are used to illustrate the methodology. Similarities and differences with other methods are discussed. Highlights: Novel methodology for full-scale friction resistance assessment. Step by step practical guideline. Case study demonstrating the proposed methodology. Comparison between different methodologies.